Historical self-governance and norms of cooperation - Devesh Rustagi (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2022)
Does self-governance, a hallmark of democratic societies, foster or erode norms of generalized cooperation? Does this effect persist, and if so, why? I investigate these questions using a natural experiment in Switzerland. In the middle-ages, the absence of an heir resulted in the extinction of a prominent noble dynasty. As a result, some Swiss municipalities became self-governing, whereas the others remained under feudalism for another 600 years. Evidence from a behavioral experiment, World Values Survey, and Swiss Household Panel consistently shows that individuals from historically self-governing municipalities exhibit stronger norms of cooperation today. Referenda data on voter-turnout, women's suffrage, and minority citizenship, allow me to trace these effects on individually costly and socially beneficial actions for over 150 years. Furthermore, norms of cooperation map into prosocial behaviors like charitable giving and environmental protection. Uniquely, Switzerland tracks every family's place of origin in registration data, which I use to demonstrate persistence from cultural transmission in a context of historically low migration.
Keywords: D02; H41; N43; Z10; 330; Self-governance; norms of cooperation; cultural transmission; referendum; public goods game; Switzerland